The cost-effectiveness of Cochlear implants in Swedish adults - Mutsa Gumbie; Emma Olin; Bonny Parkinson; Ross Bowman; Henry Cutler (BMC, 2021)
Abstract Background Research has shown unilateral cochlear implants (CIs) significantly improve clinical outcomes and quality of life in adults. However, only 13% of eligible Swedish adults currently use a unilateral CI. The objective was to estimate the cost-effectiveness of unilateral CIs compared to a hearing aid for Swedish adults with severe to profound hearing loss. Methods A Markov model with a lifetime horizon and six-month cycle length was developed to estimate the benefits and costs of unilateral CIs from the Swedish health system perspective. A treatment pathway was developed through consultation with clinical experts to estimate resource use and costs. Unit costs were derived from the Swedish National Board of Health and Welfare and the Swedish Association of Local Authorities and Regions. Health outcomes were reported in terms of Quality Adjusted Life Years (QALYs). Results Unilateral CIs for Swedish adults with severe to profound hearing loss are likely to be deemed cost-effective when compared to a hearing aid (SEK 140,474 per QALY gained). The results were most sensitive to the age when patients are implanted with a CI and the proportion of patients eligible for CIs after triage. Conclusions An increase in the prevalence of Swedish adults with severe to profound hearing loss is expected as the population ages. Earlier implantation of unilateral CIs improves the cost-effectiveness among people eligible for CIs. Unilateral CIs are an efficacious and cost-effective option to improve hearing and quality of life in Swedish adults with severe to profound hearing loss.